Kadar low density lipoprotein (LDL) tinggi berhubungan dengan peningkatan severitas sindrom koroner akut - Irma Ersalina Br Karo; Ida Bagus Rangga Wibhuti; I Nyoman Wiryawan (Intisari Sains Medis, 2020)
Background: Acute coronary syndrome (ACS) is a collection of symptoms that caused by disruption of coronary arteries so that decreasing the oxygen levels to the heart muscle (myocardium). Low-density Lipoprotein (LDL) is a lipid-carrying lipoprotein with the strongest predisposing factor compared to other cholesterol in supporting the formation of atheroma plaques in blood vessels that flow through the heart muscle in patients with acute coronary syndrome.Methods: This study is an analytic cross-sectional observational study aimed at seeing whether there is a relationship between levels of Low Density Lipoprotein (LDL) with an increase in severity of acute coronary syndrome. The population of this study were patients with a diagnosis of acute coronary syndrome at Sanglah Hospital Denpasar from July 2018 – January 2019. The relationship between LDL levels and severity of acute coronary syndrome was analyzed using Spearman correlation test and multivariate analysis in the form of discriminant analysis to analyze the relationship of LDL levels with severity of acute coronary syndrome compared with other risk factors as confounding variables.Results: Spearman correlation test showed that there was a significant positive relationship between LDL levels and severity of acute coronary syndrome with p = 0.01 and Spearman’s correlation coefficient of +0.365. The result of the study of discriminant analysis test also showed that there was a significant positive relationship between LDL levels and severity of acute coronary syndrome after being analyzed along with confounding variables with a value of p = 0.004.Conclusions: There was a significant positive relationship between LDL levels and severity of acute coronary syndrome at RSUP Sanglah Latar Belakang: Sindrom koroner akut merupakan suatu sekumpulan gejala yang disebabkan adanya gangguan pada arteri koronaria sehingga kadar oksigen menuju otot jantung (miokardium) mengalami penurunan. Low-Density Lipoprotein (LDL) merupakan lipoprotein pengangkut lipid dengan faktor predisposisi terkuat dibandingkan kolesterol lain dalam mendukung pembentukan plak ateroma pada pembuluh darah yang mengaliri otot jantung pada penderita sindrom koroner akut. Metode: Penelitian ini bersifat observasional cross-sectional analitik yang bertujuan untuk melihat apakah terdapat hubungan antara kadar Low Density Lipoprotein (LDL) dengan peningkatan severitas sindrom koroner akut.  Populasi dari penelitian ini merupakan pasien dengan diagnosis sindrom koroner akut di RSUP Sanglah Denpasar pada Juli 2018 – Januari 2019. Hubungan antara kadar LDL dengan severitas sindrom koroner akut dianalisis menggunakan uji korelasi Spearman serta analisis multivariat berupa uji analisis diskriminan untuk menganalisis hubungan kadar LDL dengan severitas sindrom koroner akut dibandingkan dengan faktor resiko lain sebagai variabel perancu.Hasil: uji korelasi Spearman menunjukkan terdapat hubungan positif bermakna antara kadar LDL dengan severitas sindrom koroner akut dengan nilai p = 0.01 serta koefisien korelasi Spearman sebesar +0,365. Hasil penelitian pada uji analisis diskriminan juga menunjukkan terdapat hubungan positif bermakna antara kadar LDL dengan severitas sindrom koroner akut setelah dianalisis bersama variabel perancu, dengan nilai p = 0,004.Simpulan: Terdapat hubungan yang positif yang bermakna antara kadar LDL dan severitas sindrom koroner akut pada pasien sindrom koroner akut di RSUP Sanglah